Three dimensional gait analysis in patients with symptomatic component mal-rotation after total knee arthroplasty - Maier, Michael Wolfgang; Aschauer, Stefan; Wolf, Sebastian Immanuel; Dreher, Thomas; Merle, Christian; Bitsch, Rudi G. (International orthopaedics, 2019)
PurposePurpose of the present cohort study was the determination of lower body function and rotation in patients with symptomatic component mal-rotation after total knee arthroplasty using instrumented 3D gait analysis.MethodsA consecutive series of 12 patients (61.3 years ± 11.4 years) were included suffering under remaining pain or limited range of motion at least six months after total knee arthroplasty. A CT-scan according to the protocol of Berger et al. and instrumented 3D gait analysis were carried out including clinical examination, videotaping, and kinematic analysis using a Plug-in Gait model. Outcome variables were temporospatial parameters as well as kinematics in sagittal and transversal plane. Data for reference group were collected retrospectively and matched by age and gender.ResultsTemporospatial parameters of the study group showed decreased velocity, cadence, and step length as well as increased step time. Single limb support was reduced for the affected limb. In sagittal plane, maximum knee flexion during swing phase was reduced for the replaced knee joint. In transverse plane, there was hardly any difference between affected and non-affected limb. Compared to the reference group, both limbs show significant increased internal ankle rotation and external hip rotation. There were significant strong linear correlations between ankle rotation and hip rotation as well as ankle rotation and radiological tibial mal-rotation.ConclusionsPatients with symptomatic component mal-rotation after total knee arthroplasty showed typically functional deficits. The affected and non-affected limb showed significant increased internal ankle rotation and external hip rotation, while only the affected, replaced knee showed reduced internal knee rotation. Identification of rotational abnormalities of hip and ankle joints seems to be mandatory in TKA to identify the patient group with external hip rotation, internal ankle rotation, and an elevated risk for symptomatic rotational TKA component mal-alignment.
First online: 10 September 2018
Gesehen am 18.09.2019